[1908 Women's Basketball team] - Frank Aston::::::photographer::: (1908)
1908 women's basketball team in uniform; with coach Margaret Chase; on outdoor court. (On reverse: 'Miss Chase at one end and I at other - manager of team.' (Hazel Griffith); all members identified in caption in Polytechnic J. (v.4, no. 5, Feb. 1909)